The Role of Histopathology as a Complementary Diagnostic Tool in the Monitoring of Bovine Tuberculosis - Larenas-Muñoz, Fernanda; Sánchez-Carvajal, José M.; Galán-Relaño, Ángela; Ruedas-Torres, Inés; Vera-Salmoral, Eduardo; Gómez-Gascón, Lidia; Maldonado, Alfonso; Carrasco, Librado; Tarradas, Carmen; Luque, Inmaculada; Rodríguez-Gómez, Irene M.; Gómez-Laguna, Jaime (Frontiers in Veterinary Science, 2022)
The diagnosis of bovine tuberculosis (bTB) is based on the single intradermal tuberculin test (SIT), interferon gamma and compulsory slaughter of reactor animals. Culture and PCR from fresh tissue are regarded as gold standard techniques for post-mortem confirmation, with the former being time-consuming and presenting moderate to low sensitivity and the latter presenting promising results. Histopathology has the advantage to identify and categorize lesions in both reactor and non-reactor animals. Therefore, this study aims to highlight the role of histopathology in the systematic diagnosis of bTB to shorten the time to disclose positive animals. Blood (212) and lymph node (681) samples were collected for serological, bacteriological and histopathological analyses from a total of 230 cattle subjected to the Spanish bTB eradication program. Seventy-one lymph nodes and 59 cattle yielded a positive result to bacteriology, with 59 lymph nodes and 48 cattle presenting a positive result to real-time PCR from fresh tissue. Roughly 19 % (40/212) of sera samples gave a positive result to ELISA. TBL were observed in 11.9 % (81/681) of the lymph nodes and 30.9 % (71/230) of cattle. Noteworthy, TBL were evidenced in 18 out of 83 SIT- and real-time PCR and bacteriology negative animals, with 11/18 disclosing a positive result to Ziehl-Neelsen technique and two of them to ddPCR from paraffin blocks targeting IS6110. Six out of this 11 ZN+ corresponded with mesenteric LN and were confirmed positive to paratuberculosis. Histopathology yielded a sensitivity of 87.5 % (CI95 78.1 % - 96.9 %) and a specificity of 84.1 % (CI95 78.7 % – 89.4 %) with a good agreement (κ = 0.608) when compared with real-time PCR. Our results confirm that histopathology allows a rapid confirmation of real-time PCR and bacteriology emphasizing its contribution to bTB control and monitoring.